2017
DOI: 10.1039/c6nj03940e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiproliferative activity of sulfa-Michael adducts and thiochromenes derived from carbohydrates

Abstract: The synthesis of new carbohydrate-derived 3-nitro-2H-thiochromenes with potential antiproliferative activity is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Absolute configuration of C-2 in the 3-nitro-2H-chromene 5a has been unambiguously determined by X-ray diffraction crystallography (Cambridge Crystallography Data Centre 1818887) ( Figure 2). This has allowed us to confirm a correlation previously established by our group between the value of the coupling constant J1',2 and the configuration at C-2 in structurally-related compounds bearing a peracetylated carbohydrate moiety, such as 3-nitro-1,2-dihydroquinolines [21] and 3-nitro-2H-thiochromenes [22]. Thus, for those carbohydrate chains with D-galacto-configuration, J1',2 is large (5-10 Hz) if C-2(S), and small (0-2 Hz) if C-2(R), and just the opposite for D-manno-configuration chains ( Table 2).…”
Section: Chemistrysupporting
confidence: 82%
See 1 more Smart Citation
“…Absolute configuration of C-2 in the 3-nitro-2H-chromene 5a has been unambiguously determined by X-ray diffraction crystallography (Cambridge Crystallography Data Centre 1818887) ( Figure 2). This has allowed us to confirm a correlation previously established by our group between the value of the coupling constant J1',2 and the configuration at C-2 in structurally-related compounds bearing a peracetylated carbohydrate moiety, such as 3-nitro-1,2-dihydroquinolines [21] and 3-nitro-2H-thiochromenes [22]. Thus, for those carbohydrate chains with D-galacto-configuration, J1',2 is large (5-10 Hz) if C-2(S), and small (0-2 Hz) if C-2(R), and just the opposite for D-manno-configuration chains ( Table 2).…”
Section: Chemistrysupporting
confidence: 82%
“…Based on the quantitative structure-activity relationship studies carried out by González-Díaz et al [23], from which it is concluded that more than 50% of the biological activity of the evaluated compounds lies in the trans-nitroolefin system, and confirmed by Steinfelder et al [13] and our own group [21,22,24], structures of 3-nitro-2H-chromenes at positions 2, 6 and 8 were modified to evaluate how it affected the antiproliferative activity.…”
Section: Scheme 2 Deacetylation Of 3-nitro-2h-chromenes 5dementioning
confidence: 99%
“…7 Representative examples of biologically relevant natural products and new chemical entities (NCEs) derived from the 3-methyleneisoindolin-1-one core are AKS 186 (I), 8 fumaridine (II), 9 narceine imide (III), 10 fumaramidine (IV), 11 fumaramine (V), 12 (R)-PD 172939 (dopamine D4 antagonist) (VI), 13 lennoxamine (VII), 14 aristoyagonine (VIII), 15 allosteric agent (IX), 16 and (S)-pazinaclone (X) 17 (Figure 1). In addition to methyleneisoindoline-1-ones, derivatives of thiochromene-4-imines also show a myriad of potential biological activities, such as antiproliferative, 18 antiemetic, 19 antioxidant, 20 antibacterial, 21 and anti-HIV, 22 which intensify the importance of new suitable approaches for the synthesis of these derivatives. One of the most efficient and convenient methods for the synthesis of methyleneisoindoline-1-ones and thiochromene-4-imines analogues include the ligand-promoted transition metal-catalyzed carbon−carbon or carbon-heteroatom coupling reaction, followed by additive cyclization on the triple bond.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Substituted thiochromenes and their analogues have been widely found in a myriad of bioactive natural products and synthetic compounds. In particular, these sulfur-containing scaffolds usually exhibit vital and special properties such as antiemetic, antiproliferative, antibacterial, and antioxidant activities, which makes them highly attractive objects for synthetic application and pharmaceutical industry. A representative example of natural products with thiochromene units suggests that Tetratolol possesses significant antidepressant activity .…”
mentioning
confidence: 99%
“…Recently, Kurahashi and Matsubara et al developed Ni­(cod) 2 -catalyzed decarbonylative cycloaddition of thioisatins with internal alkynes to afford 2,3-disubstituted thiochromones (Scheme , path b) . In 2012, Yang and co-workers reported the successful reaction of 1-(2-iodophenyl)-3-phenylprop-2-yn-1-one and sodium sulfide for the generation of 2-phenyl-4 H -thiochromen-4-one in good yields through the Ullmann-type coupling to form a C­(sp)-sulfur bond followed by Michael addition cyclization (Scheme , path c) . Furthermore, the dehydrogenation of 2-phenylthiochroman-4-one offers a simple and concise strategy using appropriate oxidizing agents such as DDQ, I 2 , and PhI­(OAc) 2 (Scheme , path d) …”
mentioning
confidence: 99%